The relationship among femoral neck angle and BMD, and lower extremity injury incidence in elite athletes: Based upon gender - Lee, N.-K.; Kim, J. K.; Kim, E.-J.; Ki, S.-K.; Choa, I. H.; Cho, J. Y.; Lee, M.-S. (International Journal of Applied Sports Sciences, 2011)
The purpose of this study was to assess the relationships between femoral neck angle and bone mineral density (BMD) and lower extremity injury incidence, and to show what differences exist between various sports populations based on gender. 129 athletes from the Korea National Sports University (81 males, 48 females) participated in this study. DXA hip joint scan was conducted and an injury history questionnaire was used. There were no significant differences in age, weight, height, and leg length in either gender. There was no significant gender difference in femoral neck angle (55.05±4.11°in males, 55.17±2.83° in females). Femoral neck BMD showed a significant gender difference (1.27±0.20 g/cm2 in males, 1.14±0.15 g/cm2in females). There was no interaction in femoral angle based upon sports type and gender; however, there was a significant interaction in femoral neck BMD based upon sports type and gender (F(11,4)=4.29, p=0.03). Although lower limb injury incidence increased by 12% in male and 74% in female when femoral neck angle was over 54°, there was no significant relationship in femoral neck angle and injury incidence. Lower extremity injury incidence was decreased by 28% in males and 47% in females when male athletes had a BMD over 1.19 g/cm2 and females over 1.08 g/cm2 without a significant difference. Although there was no significant difference in femoral neck angle based upon sports type and gender, there was a significant difference in femoral neck BMD. In addition, there was no significant relationship in femoral neck angle and BMD related to injury in this study.